Estratégia de modelagem da dinâmica de controladores para controle de AGV - Oliveira, Diogo Puppim de (2018)
In industrial environments, the use of robotics is essential to prove an efficient response and to use the demands of this sector. In particular, through the use of AGV (Automated Guided Vehicle), industrial motors for transporting materials indoors and outdoors in the industrial sector. As accomplishments of the permitted activities for a vehicle sensing, navigation and control system through the operators. These systems can be represented by mathematical modeling and simulated using software. This dissertation aims to present the representation of AGVs for the use of vehicle agents display model that will represent a virtual environment modeled in Unity3D. This strategy aims to contribute to the tuning process of the real vehicle by using the tuning made in the simulated environment employed in the real environment.